Persistent complex bereavement disorder: clinical utility and classification of the category proposed for Diagnostic and Statistical Manual of Mental Disorders, 5th edition. Issue 1 (18th January 2016) - Shimizu, Kanako; Kikuchi, Senichiro; Kobayashi, Toshiyuki; Kato, Satoshi
Abstract : Aim: Persistent complex bereavement disorder (PCBD) was proposed as a bereavement‐related clinical category in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition, which included the disorder among conditions for further study. This is an independent clinical category in which intense yearning for the deceased continues for at least 12 months. However, the diagnostic features are still inconclusive. We suggest a variation of PCBD for making category from our clinical experiences. Method: We presented two representative case studies in which grief caused by bereavement was observed as the root of the pathological condition. We examined the disorder's pathological conditions, diagnoses, and appropriate treatments based on the cases we experienced. Results: Both cases involved elderly women who lost their spouse through illness and experienced prolonged grief for an extended period, resulting in hospital admission. Based on the two cases, we believe that PCBD can also include a psychotic type with hallucinations as a major symptom. While studying PCBD, we took into account specific cultural characteristics of Japanese people and their present day social environment. Conclusions: Such cases would be suggestive when determining the PCBD clinical category in the future. PCBD is considered to be clinically very useful, especially in an extremely aged society as seen in developed countries, including Japan.